2015
DOI: 10.1038/pr.2015.70
|View full text |Cite
|
Sign up to set email alerts
|

IUGR prevents IGF-1 upregulation in juvenile male mice by perturbing postnatal IGF-1 chromatin remodeling

Abstract: Background: Intrauterine growth restriction (IUGR) offspring with rapid catch-up growth are at increased risk for early obesity especially in males. Persistent insulin-like growth factor-1 (IGF-1) reduction is an important risk factor. Using a mouse model of maternal hypertension-induced IUGR, we examined IGF-1 levels, promoter DNA methylation, and histone H3 covalent modifications at birth (D1). We additionally investigated whether prenatal perturbations could reset at preadolescence (D21). Methods: IUGR was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Many studies have demonstrated that intrauterine growth restriction is associated with epigenetic changes in different tissues of the offspring [18,[128][129][130][131][132][133][134][135][136], and several implicate epigenetic mechanisms in pancreatic β-cell failure and development of T2D [13,15,17,135,[137][138][139][140]. In our IUGR model, we have previously demonstrated in adult rats that IUGR induces genome-wide changes in DNA methylation at key loci in islets [23].…”
Section: Discussionmentioning
confidence: 85%
“…Many studies have demonstrated that intrauterine growth restriction is associated with epigenetic changes in different tissues of the offspring [18,[128][129][130][131][132][133][134][135][136], and several implicate epigenetic mechanisms in pancreatic β-cell failure and development of T2D [13,15,17,135,[137][138][139][140]. In our IUGR model, we have previously demonstrated in adult rats that IUGR induces genome-wide changes in DNA methylation at key loci in islets [23].…”
Section: Discussionmentioning
confidence: 85%
“…Such a lack of knowledge not only impedes our ability to counsel families about mechanisms of disease, but also hinders our ability to design therapy targeted at improving learning and memory function. Recognizing this gap, our laboratory developed a mouse model of IUGR that closely mimics human IUGR (11,12,(18)(19)(20) in order to dissect the functional, cellular, and molecular phenotypes of the developing IUGR hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…While, as noted previously, this model of placental insufficiency does demonstrate decreased severity of pre-retinal neovascularization in the OIR model, there are limitations to this approach including the extreme degree and abrupt onset of hemodynamic insufficiency, which likely does not fully recapitulate preeclamptic pathophysiology now believed to be a systemic condition [186]. Alternative models, including chronic systemic delivery of a thromboxane A2 analog which is commonly overproduced in preeclampsia, represents a more systemic model of preeclamptic pathophysiology and thus, may better inform relative to the human condition [192][193][194].…”
Section: A Novel Model Of Natural Rop Protectionmentioning
confidence: 99%